A COMPARISON OF RISK FACTORS OF DENGUE HEMORRHAGIC FEVER OUTBREAKS BETWEEN URBAN AND RURAL AREAS DURING THE COVID-19 PANDEMIC - Peri Arista, I Gede; Sawitri, Anak Agung Sagung; Suganda Yatra, I Made (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACTThe incidence of Dengue Hemorrhagic Fever (DHF) in Buleleng District during COVID-19 pandemic was very high. Mortality cases in 2021 will double from 2020. We conducted a case-control study in two sub-districts Buleleng District. A total of 143 samples were obtained by total sampling divided into cases and controls traced from February 1-28, 2021. Cases were individuals diagnosed by the hospital. Controls were individuals selected from the case environment and did not experience symptoms of DHF. We collected data door-to-door and data from a cohort of DHF sufferers. We processed and analyzed data using the IBM SPSS version 22 application. Inferential analysis used Chi-Square or Fisher-Exact statistical tests. We found 76 cases of DHF and 2 of them died. AR in urban areas was higher than rural areas with 4 per 10,000 and a CFR of 0.62%. A total of 45 cases were male. A total of 46 cases were in the young age group. The presence of larvae (OR: 2.01 95%CI: 1.3- 3.03), open containers (OR: 2.2 95%CI: 1.2-4.2), open rubbish bins (OR: 3.1 95%CI: 1.7-5.4) in urban areas and the presence of larvae (OR: 2.5 95% CI: 1.1-5.3), open containers (OR: 2.5 95% CI: 0.8-8.1) in rural areas were significantly associated with DHF outbreaks during the COVID-19 pandemic. The presence of larvae, open containers, and open rubbish bins are associated with DHF outbreaks during the COVID-19 pandemic. It is necessary to intensify surveillance approaches and community empowerment in eradicating mosquito nests to limit the area of transmission. ABSTRAKKejadian Demam Berdarah Dengue (DBD) di Kabupaten Buleleng pada masa pandemi COVID-19 sangat tinggi. Kasus kematian tahun 2021 meningkat dua kali lipat dari tahun 2020. Kami melakukan penelitian kasus kontrol pada dua kecamatan Kabupaten Buleleng. Sebanyak 143 sampel diperoleh dengan total sampling dibagi menjadi kasus dan kontrol yang ditelusuri mulai tanggal 1-28 Februari 2021. Kasus adalah individu yang didiagnosis oleh rumah sakit. Kontrol adalah individu yang dipilih dari lingkungan kasus dan tidak mengalami gejala DBD. Kami mengumpulkan data secara door to door dan dari data kohort penderita DBD. Kami mengolah dan menganalisis data menggunakan aplikasi IBM SPSS versi 22. Analsisis inferensial menggunakan uji statistik Chi-Square ataupun Fisher-Exact. Kami menemukan 76 kasus DBD dan 2 diantaranya meninggal dunia. AR di daerah perkotaan lebih tinggi dibandingkan pedesaan dengan 4 per 10.000 dan CFR 0,62%. Sebanyak 45 kasus adalah laki-laki. Sebanyak 46 kasus berada pada kelompok usia muda. Keberadaan jentik (OR: 2.01 95%CI: 1.3-3.03),kontainer terbuka (OR: 2.2 95%CI: 1.2-4.2),tempat sampah terbuka (OR: 3.1 95%CI: 1.7 -5.4) di daerah perkotaan dan keberadaan jentik (OR: 2,5 95% CI: 1.1-5.3), kontainer terbuka (OR: 2,5 95% CI: 0.8-8.1) di daerah perdesaan secara signifikan berhubungan dengan wabah DBD pada masa pandemi COVID-19. Keberadaan jentik, kontainer terbuka dan tempat sampah terbuka berhubungan dengan wabah DBD pada masa pandemi COVID-19. Pendekatan surveilans aktif dan pemberdayaan masyarakat dalam pemberantasan sarang nyamuk perlu dilakukan untuk membatasi daerah penularan.